2014
DOI: 10.3354/ame01694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enhanced temperature and ultraviolet B radiation on a natural plankton community of the Beagle Channel (southern Argentina): a mesocosm study

Abstract: Marine planktonic communities can be affected by increased temperatures associated with global climate change, as well as by increased ultraviolet B radiation (UVBR, 280− 320 nm) through stratospheric ozone layer thinning. We studied individual and combined effects of increased temperature and UVBR on the plankton community of the Beagle Channel, southern Patagonia, Argentina. Eight 2 m 3 mesocosms were exposed to 4 treatments (with 2 replicates) during 10 d: (1) control (natural temperature and UVBR), (2) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The time of year and the small change in Chl a over during CAPRICORN ( Figure S7) suggest that the phytoplankton community was in a plateau-like period after a bloom. The composition of the community was likely shifting from larger to smaller phytoplankton species, while bacteria and virus numbers may have been higher, as typically observed during that phase of the biological succession (e.g., Moreau et al, 2014). Differences in the biological state of the ocean during this campaign and that during the MHD measurement add complexity to a comparison of n s .…”
Section: Inps Measured During Capricornmentioning
confidence: 75%
“…The time of year and the small change in Chl a over during CAPRICORN ( Figure S7) suggest that the phytoplankton community was in a plateau-like period after a bloom. The composition of the community was likely shifting from larger to smaller phytoplankton species, while bacteria and virus numbers may have been higher, as typically observed during that phase of the biological succession (e.g., Moreau et al, 2014). Differences in the biological state of the ocean during this campaign and that during the MHD measurement add complexity to a comparison of n s .…”
Section: Inps Measured During Capricornmentioning
confidence: 75%
“…For example, Buma et al (2001) found that a rapid accumulation of DNA damages occurred when phytoplankton was exposed to an average UVBR daily dose of 35.6 KJ m À2 day À1 , which is in the same range than the average UVBR daily doses observed in the present study (36.6 AE 10.6 KJ m À2 day À1 from November to February). In addition, UVBR may have an impact on the structure and function of microbial food webs, leading to small cell-dominated communities (Mostajir et al, 1999;Ferreyra et al, 2006) although the absence of UVBR effects on the structure of planktonic communities has also been observed (Moreau et al, 2014).…”
Section: Coincidence Between the Ozone Hole And Early Sea Ice Retreatmentioning
confidence: 99%
“…12888-05, Mo Bio Laboratories, Carlsbad, CA, USA). Bacterial community composition was analyzed on each sample according to the PCR-DGGE procedure described in Moreau et al [30]. Briefly, PCR amplification of the 16S rDNA gene was performed using the universal primers 341F-GC and 907R according to Schäfer and Muyzer [31].…”
Section: Bacterial Community Composition In Biofilmmentioning
confidence: 99%